Atividade larvicida da Persea americana (Lauracea) sobre Aedes aegypti (Diptera, Culicidae) evidenciada por modificações morfohistológicas - Guimarães, Antonella Del Buono (2014)
Dengue has impact on public health of the intertropical regions of the world and its main vector Aedes aegypti. The measures most commonly used to control this vector, so far, are the synthetic insecticides, which applied on a large scale for a long period, did show resistance. Thus, chemical compounds from plants can be substitutes for synthetic insecticides, with the advantages of resistance retardation, due to the complexity of its components, easy degradation, lower toxicity to man and to be a safer alternative to the environment . Assays crude ethanol extract (cee) of Persea americana stem bark were performed in polystyrene cups, solutions containing 100 ppm of P. americana cee, previously dissolved in dimethylsulfoxide (DMSO) and water public Goiânia system. In each glass were placed 5 larvae of 3rd stage (L3) of the mosquito Aedes aegypti. The study was made of morfohistológic modifications from observations made with 4, 8, 12, 16, 20, 24 and 48 h treatment with the cee. In each period, the larvae were collected, fixed, dehydrated, infiltrated and embedded in historesin. of 3μm thick cuts were made in microtome semiautomatic, stained with hematoxylin / eosin (HE), analyzed and photomicrographed under a light microscope. For scanning electron microscopy (MEV) the treated and control larvae were fixed, dehydrated, dried in a critical point apparatus, metallized and analyzed in electron microscope. The morfohistológic changes were observed from 24 hours after treatment of larvae L3 with P. americana stem bark cee. The analysis of histological sections of the midgut of Ae. aegypti in light microscopy showed the presence of vacuoles in the cytoplasm of epithelial cells, large amount of secretion and folding of membrane peritrophic larvae treated for 48 hours. There was extrusion whole food content together with peritrophic matrix, thus suggesting the P.americana. toxic action on the gut of the larvae. These changes did not occur in the control group. There was no evidence of external changes by MEV.